Search for vector-like quarks in events with two oppositely charged leptons and jets in proton-proton collisions at root s=13TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Ambrogi,F; Asilar,E; Bergauer,T; Brandstetter,J; Dragicevic,M; Eroe,J; Escalante,Del Valle A; Flechl,M; Fruehwirth,R; et al. (European Physical Journal C: Particles and Fields, 2019)
A search for the pair production of heavy vector-like partners T and B of the top and bottom quarks has been performed by the CMS experiment at the CERN LHC using proton–proton collisions at s√=13TeV. The data sample was collected in 2016 and corresponds to an integrated luminosity of 35.9fb−1. Final states studied for TT¯¯¯¯ production include those where one of the T quarks decays via T→tZ and the other via T→bW, tZ, or tH, where H is a Higgs boson. For the BB¯¯¯¯ case, final states include those where one of the B quarks decays via B→bZ and the other B→tW, bZ, or bH. Events with two oppositely charged electrons or muons, consistent with coming from the decay of a Z boson, and jets are investigated. The number of observed events is consistent with standard model background estimations. Lower limits at 95% confidence level are placed on the masses of the T and B quarks for a range of branching fractions. Assuming 100% branching fractions for T→tZ, and B→bZ, T and B quark mass values below 1280 and 1130GeV, respectively, are excluded.